Chiral Anomaly, Triangle Loop and the \(γγ^*→ π^0\) Transition Form Factor - Nang, Pham Tri; Yem, Pham Xuan (Communications in Physics, 2013)
The recent BaBar measurements of the \(γ +γ ^ * → π ^0 \) form factor show spectacular deviation from perturbative QCD computations for large space-like \(Q^2\). At 34 GeV\(^2\) the data are more than 50% larger than theoretical predictions. Stimulated by these new experimental results, we revisit our previous paper on triangle loop effects related to chiral anomaly, and apply our method to the \(γ +γ ^ * → π ^0 \) transition form factor measured in the single tag mode \(e^ + +e^ - → e^ + + e^ - +π ^0 \) with one highly virtual photon \(γ ^ * \). The resultant form factor \(F(Q^2)\)- which depends on only one parameter (the mass \(m\) of up, down quark circulating in the triangle loop) behaves like \((m^2/Q^2) × [(Q^2/m^2)]^2\)- shows a striking agreement with BaBar data for \(m ≈ 132\) MeV. The rising logarithm squared form factor, surprisingly unnoticed in the literature, is in sharp contrast with the rather flat ones derived from perturbative QCD approaches.